PENERAPAN SANKSI PIDANA ADAT DALAM PENYELESAIAN PERKARA PIDANA RINGAN DI DESA SINTONG BAKTI KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR - Muhammad Fahlebvy; Erdianto Erdianto; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The Unitary State of the Republic of Indonesia is a country that has many tribes andvarious cultures that make us a nation rich in values that are hereditary and are inheritedfrom generation to generation. The 1945 Constitution serves as the basis and reference inevery regulation making and implementation in the Republic of Indonesia. Article 18 bparagraph 2 of the 1945 Constitution recognizes and respects customary law communityunits and their traditional rights as long as they are still alive and in accordance with thedevelopment of society and the principles of the Unitary State of the Republic ofIndonesia, which are regulated in the law. In this case the State has clearly stated that itrecognizes and provides clear rules regarding customary law communities where thiscustom is an unwritten rule and becomes a living value in the midst of Indonesian society.This research belongs to sociological legal research, namely research that wants to seethe correlation between law and society with the gap between das sollen and das sein.This research was conducted in the areas of Sintong Bakti Village and Sintong Village,while the population and sample were the Traditional Heads of Sintong Bakti Village,Head of Sintong Bakti Village, Community Leaders and the Sintong Bakti VillageCommunity. The data sources used are primary data, secondary data and tertiary datawith data collection techniques by means of interviews and literature review.From the results that the settlement of minor cases that occurred in the village of Sintongthrough customary law is very effective, because in fact the customary law in the villageof Sintong still exists and is highly respected by the people in this village of Sintong. Andthe settlement of minor crimes through customary law can regenerate the family systemin the midst of society, so that punishment is no longer made as an arena for revenge.Through this system it can be a means to maintain local wisdom. In the application ofcustomary criminal sanctions, this becomes a challenge that customary stakeholders musthave the courage to take, considering that the case is their own nephew. In terms ofimplementation, all concepts that prioritize deliberation have been carried out.Key Words: Misdemeanor Crime, Customary Crime, Traditional Deliberation